Роботизация демонстрационной модели маятника Цельнера - Кравцов, Илья Дмитриевич (Перспективы развития фундаментальных наук. Т. 7 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The work is devoted to the development of a laser indicator that allows recording small movements of a gravimeter made on the basis of a Zellner pendulum in a robotic mode. A modification of the previous version of the Zellner pendulum consists in using a semiconductor laser fixed at the end of a horizontal rod. The indicator should collect and process information about the effects of the Sun and Moon on the Earth's surface. The Zellner pendulum, fixed in the earth's crust, oscillates the horizontal rod during the movement of tectonic plates. The trajectory of the image of the laser beam fixed on a horizontal rod is recorded by the camera. Digitization of this information takes place using a program on a computer. The program allows you to track the movements of the laser beam and achieve stable operation of the indicator. The result of the indicator is displayed on a personal computer, where it can already be processed. The operation of this indicator takes place in a constant mode.